PENGARUH JUMLAH TRAFFIC TERHADAP BEBAN KERJA AIR TRAFFIC CONTROLLER (ATC) DI JAKARTA LOWER CONTROL NORTH - Puput Cristi; Faizal Zaini (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
This study aims to determine the effect of the amount of traffic (flight traffic) on the workload of air traffic guidance (ATCO) in Jakarta Lower Control North. There is a positive relationship between the amount of traffic to the workload of Air Traffic Controller (ATC) in Jakarta Lower Control North with a correlation coefficient of 0.859 and a coefficient of determination of 74%, which means that the effect of the amount of traffic on the workload of the Air Traffic Controller (ATC) in Jakarta Lower Control North is 74%, so to reduce the workload of air traffic guidance (ATCO), the Airnav Indonesia management at JATSC is sectoralization to reduce the amount of traffic that must be controlled in the Jakarta Lower Control North sector. The sector is named the Jakarta Lower Control West sector to divide the workload of air traffic guidance (ATCO) in Jakarta Lower Control North, or impose slot time distribution in accordance with the maximum capability of Airspace and ATCO especially in the Jakarta Lower Control North sector.